Indonesian English Department Students Listening Difficulties and Listening Strategies - Fachriza Amalia Rakhman; Sri Samiati Tarjana; Sri Marmanto (IJER (Indonesian Journal of Educational Research), 2019)
Listening Difficulties and Listening Strategies Perceived by EFL Learners. This study aimed at revealing listening difficulties and listening strategies perceived by Indonesian learners in English as a Foreign Language listening class. The data were collected from 6 EFL students who have studied at the English Department program in one of University in Indonesia. This research is qualitative research which used questionnaires, observation and a semi-structured interview with think-aloud protocol to gain the data. This research used a Second Language Listening Difficulties Questionnaire proposed by Anna Ching-Shyang Chang (2013) to complete the required data. The finding of the research showed that EFL Indonesian learners face difficulties related to internal and external factors. Moreover, in tackling the difficulties, the students apply listening strategies. Those listening strategies are including both cognitive and metacognitive.